A capillary flow immunoassay microchip utilizing inkjet printing-based antibody immobilization onto island surfaces—toward sensitive and reproducible determination of carboxyterminal propeptide of type I procollagen. (17th March 2016) - Fuchiwaki, Yusuke; Tanaka, Masato; Takaoka, Hiroki; Goya, Kenji
Abstract: A capillary-flow-driven microchip system requires no external power and has no moving off-chip components, in contrast with most microfluidic-based immunoassay systems which are complicated to operate and require external components. To accelerate the sensitive and reproducible determination of analytes required for practical point-of-care applications, we formed island microchannel surfaces on a microcapillary channel to allow stable antibody immobilization. The island surface was surrounded by a circular groove 10 μ m deep and 150 μ m wide and allowed uniform inkjet printing of antibody spots, complete bio-reagent replacement, and sensitive detection of luminescence intensity. Quantitative analysis of carboxyterminal propeptide of type I procollagen (PICP) concentrations using this microchannel was demonstrated between 0–600 ng·ml −1, which is adequate for the clinical estimation of PICP concentrations in the blood. This microchip system holds promise as a model diagnostic platform that is readily adaptable to hands-free operation.